Relationships between dispositional and experimentally elicited emotional reactivity, intensity, and perseveration - Boyes, Mark; Clarke, Patrick; Hasking, Penelope (2020)
© 2019 Elsevier Ltd Background: The Emotional Reactivity Intensity and Perseveration Scale (ERIPS) assesses dimensions of trait emotional reactivity, intensity, and perseveration. We aimed to further validate the ERIPS and determine whether these dimensions of trait emotion predict real-time responses to negatively and positively-valenced stimuli. Method: Undergraduate students (n = 214) completed the ERIPS and viewed a sad and amusing movie clip. Participants provided sadness/amusement ratings at seven time-points pre and post viewing the clips. Results: Higher perseveration of trait negative and positive affect was associated with slower reductions in sadness and amusement ratings after viewing the clips. Higher trait positive reactivity was associated with a larger increase in amusement after viewing the amusing clip, and a faster return to baseline amusement levels. Trait negative reactivity and negative intensity were not associated with responses to the sad clip. Trait positive intensity was not associated with responses to the amusing clip. Conclusion: Although mixed, findings provide some validation of the ERIPS and indicate that, for reactivity and perseveration at least, trait affect may be associated with variability in state affect. Future research should consider mechanisms accounting for individual differences in emotional reactivity, intensity, and perseveration, as well as their potential utility in furthering understanding of emotional disorders.